ChemInform Abstract: Three‐Component, Four‐Molecule, Ru‐Catalyzed Cascade Reactions of Indoles and Alkyl Bromides with Sodium Nitrite. Issue 28 (July 2015) - Qu, Hongen; Li, Jiuling; Li, Huiliang; Wang, Hengshan; Liu, Liangxian
Abstract (E)‐2, 3′‐bi(3H‐indol)‐3‐one O‐alkyl oximes (III), (V) are regio‐ and stereoselectively obtained.